2022
DOI: 10.1111/apt.16800
|View full text |Cite
|
Sign up to set email alerts
|

The use of, and outcomes for, inflammatory bowel disease services during the Covid‐19 pandemic: a nationwide observational study

Abstract: Background Inflammatory bowel disease (IBD) services have been particularly affected by the Covid‐19 pandemic. Delays in referral to secondary care and access to investigations and surgery have been exacerbated. Aims To investigate the use of and outcomes for emergency IBD care during the Covid‐19 pandemic. Methods Nationwide observational study using administrative data for England (2015‐2020) comparing cohorts admitted from 1 January 2015, to 31 January 2020 (pre‐pandemic) and from 1 February 2020, to 31 Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Similar trends were observed in the USA with a reduction of colorectal cancer diagnosis by about 50% 122. Emerging data capturing IBD-related procedures, investigations and hospital attendances continued to show a decrease in volume of these activities during the pandemic compared with prepandemic 123 124…”
Section: Impact Of Covid-19 On Ibdsupporting
confidence: 59%
See 1 more Smart Citation
“…Similar trends were observed in the USA with a reduction of colorectal cancer diagnosis by about 50% 122. Emerging data capturing IBD-related procedures, investigations and hospital attendances continued to show a decrease in volume of these activities during the pandemic compared with prepandemic 123 124…”
Section: Impact Of Covid-19 On Ibdsupporting
confidence: 59%
“… 122 Emerging data capturing IBD-related procedures, investigations and hospital attendances continued to show a decrease in volume of these activities during the pandemic compared with prepandemic. 123 124 …”
Section: Impact Of Covid-19 On Ibdmentioning
confidence: 99%
“…We thank Mungmunpuntipantip and Wiwanitkit for their correspondence regarding our recent paper on the use of, and outcomes for, inflammatory bowel disease services in England during the Covid‐19 pandemic. 1 , 2 We agree with them that only a proportion of patients with severe inflammatory bowel disease presented during the pandemic. This is likely due to several reasons.…”
supporting
confidence: 65%
“…Declarations of personal and financial interests : The authors' declarations of personal and financial interests are unchanged from those in the original article. 2 …”
Section: Acknowledgementmentioning
confidence: 99%
“…In their recent publication, 1 Deputy et al concluded that “There is likely a significant burden of untreated IBD in the community. Patients with IBD may experience clinical harm or protracted decreases in quality of life if care is not prioritised.” The effect of the COVID‐19 pandemic and subsequent lockdown on the medical care of patients is extensively discussed.…”
mentioning
confidence: 99%